PENGEMBANGAN MODEL PERMAINAN DRIBBLING DAN PASSING SEPAK BOLA “DODGE BALL” PADA SISWA KELAS V SD NEGERI WONOLOPO 1 KECAMATAN MIJEN KOTA SEMARANG TAHUN 2012 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
Implementation of physical education activities in elementary school Wonolopo 1 Mijen Semarangoriented various sporting activities that are improving student fitness. The problemsthat the center of attention in this study is: What form model development dribbling and passinggame football dodge ball in grade V Wonolopo SD Negeri 1. This study aims to produceproducts such as dribbling and passing game model football dodge ball for elementary schoolstudents in the learning of Physical Education, Sport and Health.This study is a research method that refers to the development of models of Borg & Gall developmentthat has been modified, namely: (1) a preliminary investigation and collection ofinformation, including field observations and literature review, (2) develop the initial productform, (3) evaluation experts using satuahli penjas and two learning experts, as well as smallgroup trials, using questionnaires and then analyzed, (4) revision of the first products, productrevisions based on the results of an expert evaluation and testing of small groups (10 students).This revision is used for the improvement of the initial products made by researchers, (5) fieldtest (30 students), (6) revision of the final product which is based on the results of field tests,(7) the end result of the development of dribbling and passing game model football dodgeballyang generated through field test revision.